21.7k views
1 vote
Solve by using substitution:

y=6x+1
y=-2+6x
(Please show your work, I really don't understand this!)

1 Answer

3 votes

Answer: no solutions


\left \{ {{y=6x + 1} \atop {y=-2+ 6x}} \right.\\\\<=>\left \{ {{-2+6x=6x+1} \atop {y=-2+6x}} \right.\\\\<=>\left \{ {{6x-6x=1+2} \atop {y=-2+6x}} \right.\\\\<=>\left \{ {{0=3} \atop {y=-2+6x}} \right.

but 0 ≠ 3 => There are no values ​​for x and y => no solutions

Explanation:

User Muaaz Rafi
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.